On The Early Research in Visuo-Motor Coordination based on Neural Networks - Campos, Tarcísio Passos Ribeiro de (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1994)
This paper presents various models that have approched the visuo-motor coordination in human beings. These selected models are based on neural networks coupled with intuitive ideas which try to explain how human beings solve the arm coordenation problem. Basically, the goals are the simulation of the circular reaction found in infants, the path planning or the solution of the inverse kinematics into a robot environment. A model proposed by the author is discussed and qualitativy analyses are made.